Modification of Load Calculation in The Dijkstra Algorithm to Achieve High Throughput and Low Latency on 5G Networks - Eko Kuncoro Adiyanto; Sri Wahjuni; Hendra Rahmawan (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
throughput for high-resolution remote video surveillance. 5G cellular network as today's most advanced wireless technology will be the perfect match for Agriculture 4.0 requirements. In its maturity process, the 5G network requires various optimizations, one of which is by making route algorithm calculation modifications in terms of determining the best route for a data packet from a data source to a data destination. To achieve this goal, it requires research in the form of experiments using network simulator. Software Define Network (SDN) as network programmability is used to modify route in Dijkstra algorithm calculation, and run several use case that simulate 5G network characteristic. By adding bandwidth utilization and latency parameters into the routing algorithm calculations, 5G requirements such as packet loss below 1% and latency below 5ms are successfully achieved. These positive results may be further tested on real 5G networks, if in the future this research also gets positive results in testing on a real 5G network, then cellular network customers will be able to experience an increase in service quality.